Overview on bio-refinery concept in Malaysia : potential high value added products from palm oil biomass - Nursia Hassan,; Ani Idris,; Akhtar, Junaid (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper presents an overview of bio-refinery concept in Malaysia emphasing on diversifying and maximizing the value of palm oil biomass feedstock to produce bio-based chemicals that demonstrated strong market growth. The oil palm mills and plantations contributes to large amounts of biomasss such as oil palm fronds (OPF), oil palm trunks (OPT) and empty fruit bunches (EFB) which are sources of renewable energy. A majority of these lignocellulosic palm oil byproducts are not effectively utilized and some parts of the biomass are utilized as biofertilizers and solid biofuels. Thus, the potential of palm oil biomass should be explored by diversifying the consumption of these biomass to produce high value added chemicals and biofuels which can generate additional revenue for the country. A number of technologies; namely biochemical conversion, pyrolysis etc. have been established to convert such biomass into a wide spectrum of biobased commodities such as biodiesel, succinic acid, lactic acid, bioethanol and polyhydroxyalkanoates (PHA). This article comprehensively reviews the potential of high value added products generated from palm oil biomass via different bio-refinery approach with special attention on the biochemical conversion process followed by their development stage towards full commercial scale. Limitations and challenges in each process were also discussed in detail.